Efficacy and safety of transcarotid compared to transfemoral approach of patent ductus arteriosus stenting in duct-dependent cyanotic heart disease - Made Satria Yudha Dewangga; Radityo Prakoso; Anna Ulfah Rahajoe; Oktavia Lilyasari (The Egyptian Heart Journal, 2023)
Abstract Background Minimally invasive transcatheter approaches were usually done for patent ductus arteriosus (PDA) with duct-dependent pulmonary circulation. There are two ways to establish vascular access, by using transfemoral either femoral vein (FV) or femoral artery (FA) and transcarotid artery (CA) with surgical cutdown approach to access the PDA and then provide good support for the balloon and the stent to be safely deployed. This study aims to compare the efficacy and safety of transcarotid with surgical cutdown compared to the transfemoral approach of patent ductus arteriosus stenting in duct-dependent cyanotic heart disease. Results Overall procedural complication rates were higher in the FA/FV approach than in the CA approach (51% vs. 30%). The incidence of acute limb ischemia in the FA approach is significantly higher than in the CA approach (P < 0.05). No acute thrombosis/occlusion of the carotid artery was assessed by carotid vascular ultrasound in 2-day series. Conclusions The transcarotid approach with surgical cutdown may offer a secure and more efficient means of accessing the PDA, particularly for those emerging from the underside of the aortic arch.